University Teachers Colleges and the education issue in Michoacan, 1917-1930 - Gutiérrez López, Miguel Ángel (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2016)
Teachers Colleges were part of the initial University project in Michoacan. Teachers Colleges were created in 1915 and were integrated into the Michoacan University in 1917, where they remained until 1930. The institution faced problems of violence and the political instability of the time. In addition to the economic crisis in the state, the University and Teachers Colleges conducted their activities in a society facing serious educational backwardness inherited from the nineteenth century.However, despite the difficulties, these institutions and their members took responsibility for training the teachers of basic education who would try to change the social reality by providing literacy.This paper presents a historical account of the role played by the teachers colleges within the initial project of Michoacan University. We make reference to the establishment of this institution and its importance in a context of social crisis resulting from the political turmoil of the time. There is also allusion to the educational issues and the role assigned to Teachers Colleges. In addition to institutional references and infomation about the social context the paper also presents some insights into the characteristics of the organization and academic functioning of the teachers colleges.